ePoster: sip and chill / Muhammad Muzakkir Mohd Zaki ... [et al.] - Mohd Zaki, Muhammad Muzakkir; Mohd Saufi, Ahmad Marzuqi; Mohd Dzaher, Mohd Aqmal Hafizi; Ab Hamid, Mohd Zulhilmi (2022)
The concept for this project was inspired by this new era of social media such as Pinterest, Instagram, Facebook, and TikTok. But, what makes this project different from the other social media companies is that this app is focused mainly on gastronomy and culinary as well as on marketing and community-making purposes. This app features almost all functions just like other social media such as pictures and video posting, chat messeges and sharing features but what makes it special is that users can create its communities that shares the same passion and interests that related with food and beverages. Sip and Chill also have a features that users can explore so many kinds of culinary hype and scenes such as new restaurant in town, food festivals, best cafes, and what's special around the city and many more.